Epidemiological analysis over 2 years at the Burn Unit of the Urgency Hospital Governor Otávio Lage de Siqueira, Goiânia, Brazil - Fabiano Calixto Fortes De Arruda; Brunna Cândida de Oliveira Castro; Jean Filipe de Medeiros; Wilson José Valadão; Gilberto Marcos dias dos Reis (Revista Brasileira de Cirurgia Plástica)
Introduction: Burns are a type of injury that is among the leading causes of mortality. The use of epidemiology helps in providing subsidies for evaluation and organization of treatment and prevention, aiming at the improvement of public health. The objective is to describe the epidemiological profile of the patients treated at the Queimados Nelson Picollo unit of the Governador Otávio Lages de Siqueira Emergency Hospital (HUGOL). Method: This study analyzed the epidemiological profile of patients, aged more than 12 years, treated by plastic surgery at the burn treatment unit, Nelson Picollo, from July 2015 to June 2017. The patients who were not admitted to the burn unit were excluded from the study. Data were collected from the MVSoul R. program. Results: A total of 375 patients visited the hospital; of these, 50% of the patients needed intensive care unit treatments. The mean duration of hospital stay was 23.08 days. The majority of the patients were males, with a mean age of 39.17 years, and the main etiological agents were inflammable liquids, mainly alcohol and gasoline. The mean burned body surface area was 24.67%. A total of 1490 surgical interventions were performed, with an average of 3.97 surgeries per patient. Forty patients died; of these, 29 had airway burns. The total number of patients with airway burns was 73. Conclusion: This study provides a profile of burns and hospitalizations in the HUGOL burns unit, which corresponds with those from other centers specialized for this type of treatment.